2017
DOI: 10.1161/strokeaha.116.015492
|View full text |Cite
|
Sign up to set email alerts
|

The Basilar Artery on Computed Tomography Angiography Prognostic Score for Basilar Artery Occlusion

Abstract: B asilar artery occlusion (BAO) comprises ≈1% of all strokes and is one of the most devastating neurological conditions associated with high risk of disability and mortality if recanalization does not occur. [1][2][3] Despite recent breakthroughs in the treatment of large vessel occlusion ischemic stroke, BAO patients were excluded from recent randomized controlled trials, 4-8 and the evidence for treatment is derived largely from small retrospective studies.9,10 The Australian Urokinase Stroke Trial is the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 27 publications
2
131
2
1
Order By: Relevance
“…Our data are in agreement with PC-CS as a predictor of outcomes; however, the presence of both PCoAs was not related to favorable outcomes in our sample. In BAT-MAN cohort, all patients were treated with acute reperfusion therapies and outcomes were analyzed at 90 days, similarly to our protocol [12]. In that study, a better accuracy of the BATMAN score over PC-CS was suggested, which is in contrast to our results [12].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Our data are in agreement with PC-CS as a predictor of outcomes; however, the presence of both PCoAs was not related to favorable outcomes in our sample. In BAT-MAN cohort, all patients were treated with acute reperfusion therapies and outcomes were analyzed at 90 days, similarly to our protocol [12]. In that study, a better accuracy of the BATMAN score over PC-CS was suggested, which is in contrast to our results [12].…”
Section: Discussionmentioning
confidence: 54%
“…In BAT-MAN cohort, all patients were treated with acute reperfusion therapies and outcomes were analyzed at 90 days, similarly to our protocol [12]. In that study, a better accuracy of the BATMAN score over PC-CS was suggested, which is in contrast to our results [12]. However, intra-arterial urokinase infusion was allowed in BAT-MAN cohort, and some included patients were not submitted to EVT.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In their multivariate analysis, an unfavorable BATMAN score (defined as <7) was independently associated with poor outcome (defined as an mRS of 4 or greater) in both derivation and validation cohorts. A BATMAN score of <7 had a sensitivity of 84% and specificity of 76% to predict a poor outcome (22). …”
Section: Thrombus Burden and Locationmentioning
confidence: 99%